1985
DOI: 10.1039/dt9850002671
|View full text |Cite
|
Sign up to set email alerts
|

Methyltin hydrides in fluorosulphuric acid

Abstract: Stannane or the methylstannanes SnMeaPnHn ( n = 1-4) react i n fluorosulphuric acid at low temperature (-90 "C) to produce SnMeSnH,+ ( n = 0-3) and 'H, 13C, and I19Sn n.m.r. spectroscopy have been used in their characterisation. Hydrogen-evolution, I19Sn n.m.r., and Mossbauer evidence is presented t o show that at higher temperatures these species decompose t o Sn2+, Sn2+ plus SnMeZ2+, and SnMe22+ depending o n the starting hydride.Stannane and the methylstannanes have been well studied by a variety of spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…Consideration of BH,, BH4-and AlH3 , A1H4-oindicates derivatives of +3.5, -27.0 and + 84.2, + 11.6 ppm/A, respectively; thus in going from SnH3+ to SnH4 one expects the derivative to decrease algebraically as observed. (15). A , ' J ( ' '~S~~/ ' H ) was found to be between -2.7 and -3.0 Hz, the average value being -2.8 ?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consideration of BH,, BH4-and AlH3 , A1H4-oindicates derivatives of +3.5, -27.0 and + 84.2, + 11.6 ppm/A, respectively; thus in going from SnH3+ to SnH4 one expects the derivative to decrease algebraically as observed. (15). A , ' J ( ' '~S~~/ ' H ) was found to be between -2.7 and -3.0 Hz, the average value being -2.8 ?…”
Section: Resultsmentioning
confidence: 99%
“…SnD,,H3-,+ (n 5 3) was prepared (15,17) by the reaction of 0.01 mol of SnD,H4-,, (H:D mole ratio = 2:3) and 4 mL of HS03F (Aldrich), which had been distilled under nitrogen, in a 10-mm 0.d. thick-walled nmr tube.…”
Section: Spin-spin Coupling Constantsmentioning
confidence: 99%
“…Lambert and Kira therefore suggested trigonal free tin cations in these experiments, contrary to the earlier proposals. 6 By using an empirical shift correlation between tin and silicon,7 as shown in Fig. 1, one should be able to derive a crude prediction of chemical shifts of new complexes as well as obtain an estimate of the Sn chemical shift of the free trigonal stannyl ion.…”
mentioning
confidence: 99%
“…[HO{B(C 6 F 5 ) 3 } 2 ] − Ar = 2,6-diisoPrC 6 692 Lambert and Kuhlmann 693 [Bu 3 Sn þ H(C 6 F 5 ) 3 B À ], and Kira et al 694 (Bu 3 Sn þ TFPB À ) exhibit 119 Sn NMR chemical shifts in the region d 119 Sn 322-360. Using the empirical correlation between 29 Si and 119 Sn chemical shifts, Arshadi et al 695 concluded that these claimed stannylium ions have, in fact, little ionic character (assuming linear relationship between 29 Si and 119 Sn chemical shifts, the chemcial shift of d 29 Si 225 corresponds to d 119 Sn 1100).…”
Section: Si Phmentioning
confidence: 99%